Treatment with pyridostigmine bromide in a canine with difficulty emptying the bladder in a canine positive for acquired myasthenia gravis - Mundo, Silvia; Montoro, Andrea; Kim, Angélica; Ruidiaz, Viviana; Suraniti, Adriana (Spei Domus, 2020)
Introduction: Acquired myasthenia gravis (AGM) is an immune-mediated disease that presents a decrease in the number or functionality of acetylcholine receptors at the nicotinic level. This leads to less effective muscle contraction. The most common clinical manifestation is episodic weakness that increases with exercise and improves with rest. Other clinical signs are: regurgitation and voice changes. The purpose of this report is to describe a canine, female with dysuria without stranguria who was taken to the Hospital School of Veterinary Medicine of the University of Buenos Aires. Methods: blood and urine tests, urine cultures, spinal radiographs, abdominal ultrasound, electromyography (EMG) of the anal sphincter and repetitive stimulation were performed. Antibodies against acetylcholine receptors (ACRA) were measured. Results: blood tests, urinalysis, spinal radiographs and abdominal ultrasound were normal. Urine cultures were negative. Anal sphincter EMG was preserved. Repetitive stimulation EMG was compatible with MGA. The patient was ACRA positive and his response to treatment with pyridostigmine bromide (BRP) was favorable. Conclusions: include MGA in canine patients with dysuria in the deferential diagnosis.